Determinants of Turnover Intention: Job Satisfaction, Work-Family Conflict, and Organizational Commitment - Sarianja, Suherdian Septa; R, Wahyu Rahmadia; Rahayu, Witri; Syafwandi, Syafwandi (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Putra Indonesia YPTK, 2025)
This research aims to empirically examine the direct and indirect effects of Work-Family Conflict and Organizational Commitment on Turnover Intention, with Job Satisfaction as mediating variables. The study employs a quantitative approach. The population comprises permanent employees of PT Semen Padang., with a sample size of 319 employees. The sampling method uses proportional sampling. The analysis method used is Partial Least Squares (PLS) analysis with the SmartPLS application. The results indicate that organisational commitment significantly influences job satisfaction. Additionally, work-family conflict and job satisfaction have a significant partial effect on turnover intention. Job satisfaction mediates the relationship between organisational commitment and turnover intention. This research provides suggestions to PT Semen Padang to increase employee commitment by providing better support and recognition to increase job satisfaction. Then the company must implement policies that support balance between work and family to reduce conflict.